Голчастi кристали напівпровідників A²B⁶ i Si - Витрихівський, М. (Праці наукового товариства ім. Шевченка, 2011)
The paper is devoted to the technological peculiarities of growing the A²B⁶ needle crystals the solid solutions on its basis as well as silicon crystals originally developed and realized by the author. Physical properties of these materials are explored in dependence on composition and form of growth. These crystals may be used in quantum electronics.